2019
DOI: 10.1111/evo.13807
|View full text |Cite
|
Sign up to set email alerts
|

Legacy of prior host and soil selection on rhizobial fitness in planta

Abstract: Measuring selection acting on microbial populations in natural or even seminatural environments is challenging because many microbial populations experience variable selection. The majority of rhizobial bacteria are found in the soil. However, they also live symbiotically inside nodules of legume hosts and each nodule can release thousands of daughter cells back into the soil. We tested how past selection (i.e., legacies) by two plant genotypes and by the soil alone affected selection and genetic diversity wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 65 publications
3
26
0
Order By: Relevance
“…Genomic complexity could influence genetic variance and evolutionary trajectories, as in multi-nucleate arbuscular mycorrhizal fungi [60]. Furthermore, our model comprises a panmictic population in a constant environment; yet environments fluctuate in space and time, especially for horizontally transmitted microbes [61], and such variation in selection could alter evolution [62] or generate spatial correlations between host and symbiont breeding values. In our model, partnerships form at random, so genetic correlations do not arise pre-selection through spatial structure or other mechanisms (e.g.…”
Section: Closing Remarksmentioning
confidence: 99%
“…Genomic complexity could influence genetic variance and evolutionary trajectories, as in multi-nucleate arbuscular mycorrhizal fungi [60]. Furthermore, our model comprises a panmictic population in a constant environment; yet environments fluctuate in space and time, especially for horizontally transmitted microbes [61], and such variation in selection could alter evolution [62] or generate spatial correlations between host and symbiont breeding values. In our model, partnerships form at random, so genetic correlations do not arise pre-selection through spatial structure or other mechanisms (e.g.…”
Section: Closing Remarksmentioning
confidence: 99%
“…Rhizobia are best known to develop symbiotic interactions with legumes, where mutualistic relationships progress to modifications of the root architecture of the host plant by the formation of nodules where nitrogen fixation occurs [60]. Nevertheless, nonsymbiotic and even parasitic rhizobial strains can be found in abundance in rhizosphere and nonrhizospheric soils, and the resulting plant-rhizobium interaction can be determined by the genetic content of both partners and environmental pressure [61][62][63][64].…”
Section: In Vitro Assays In Vivo Assays: Tomatomentioning
confidence: 99%
“…Genomic basis of fitness alignment: One host genotype (A17) associated with more beneficial bacterial strains than the other (Burghardt et al, 2018). By looking for overlap between top GWAS candidates for plant size in single-strain inoculations and strain fitness, Epstein et al (2019) identified bacterial genes, including NifA and QueC, that may influence both traits.…”
Section: Legumes and Rhizobia: New Tools Drive Discoveriesmentioning
confidence: 99%